A quantitative proteomic analysis of cellular responses to high glucose media in Chinese hamster ovary cells. (29th April 2015) - Liu, Zhenke; Dai, Shujia; Bones, Jonathan; Ray, Somak; Cha, Sangwon; Karger, Barry L.; Li, Jingyi Jessica; Wilson, Lee; Hinckle, Greg; Rossomando, Anthony
<x xml:space="preserve">Abstract</x> A goal in recombinant protein production using Chinese hamster ovary (CHO) cells is to achieve both high specific productivity and high cell density. Addition of glucose to the culture media is necessary to maintain both cell growth and viability. We varied the glucose concentration in the media from 5 to 16 g/L and found that although specific productivity of CHO‐DG44 cells increased with the glucose level, the integrated viable cell density decreased. To examine the biological basis of these results, we conducted a discovery proteomic study of CHO‐DG44 cells grown under batch conditions in normal (5 g/L) or high (15 g/L) glucose over 3, 6, and 9 days. Approximately 5, 000 proteins were confidently identified against an mRNA‐based CHO‐DG44 specific proteome database, with 2, 800 proteins quantified with at least two peptides. A self‐organizing map algorithm was used to deconvolute temporal expression profiles of quantitated proteins. Functional analysis of altered proteins suggested that differences in growth between the two glucose levels resulted from changes in crosstalk between glucose metabolism, recombinant protein expression, and cell death, providing an overall picture of the responses to high glucose environment. The high glucose environment may enhance recombinant dihydrofolate reductase in CHO cells by up‐regulating NCK1 and down‐regulating PRKRA, and may lower integrated viable cell density by activating mitochondrial‐ and endoplasmic reticulum‐mediated cell death pathways by up‐regulating HtrA2 and calpains. These proteins are suggested as potential targets for bioengineering to enhance recombinant protein production. © 2015 American Institute of Chemical Engineers Biotechnol. Prog., 31:1026–1038, 2015